2012
DOI: 10.1107/s0907444912042072
|View full text |Cite
|
Sign up to set email alerts
|

Structures of aminophenol dioxygenase in complex with intermediate, product and inhibitor

Abstract: Dioxygen activation by nonhaem Fe(II) enzymes containing the 2-His-1-carboxylate facial triad has been extensively studied in recent years. Here, crystal structures of 2-aminophenol 1,6-dioxygenase, an enzyme that represents a minor group of extradiol dioxygenases and that catalyses the ring opening of 2-aminophenol, in complex with the lactone intermediate (4Z,6Z)-3-iminooxepin-2(3H)-one and the product 2-aminomuconic 6-semialdehyde and in complex with the suicide inhibitor 4-nitrocatechol are reported. The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
4
24
1
Order By: Relevance
“…This oxygenated intermediate also inherits the monodentate coordination status found in the previous lactone intermediate. These observations are consistent with findings in other extradiol dioxygenases that the newly formed carboxyl group binds to the iron in a monodentate fashion with the products retaining a more cyclized conformation (29,45,46).…”
Section: Hao Is Catalytically Active In the Crystalline State With Sisupporting
confidence: 92%
See 1 more Smart Citation
“…This oxygenated intermediate also inherits the monodentate coordination status found in the previous lactone intermediate. These observations are consistent with findings in other extradiol dioxygenases that the newly formed carboxyl group binds to the iron in a monodentate fashion with the products retaining a more cyclized conformation (29,45,46).…”
Section: Hao Is Catalytically Active In the Crystalline State With Sisupporting
confidence: 92%
“…A denticity change, from one to two, is observed in the product bound complex. Most of the products observed through in crystallo reaction in extradiol dioxygenases maintain a cyclized conformation (29,45,46), as seen in (E•P) I of HAO. A linearized product like (E•P) II is less commonly seen bound at the active site in dioxygenases in the degradation of aromatic molecules (40).…”
Section: Discussionmentioning
confidence: 99%
“…Prior experiments have shown that some members of the classical LigB family function as homodimers (24,28). A range of other configurations have also been described: the gallate dioxygenase GalA, a member of the classical LigB family, functions as a homotrimer (29); the APD family forms a heterodimer between active and inactive paralogs (30); and the YgiD-like family has thus far been characterized as a functional monomer in bacteria (31) and plants (32). The significance of potential multimerization in the Memo clade remains unexplored.…”
Section: Multimerizationmentioning
confidence: 99%
“…CtAPD is an extradiol ring-cleavage dioxygenase whose X-ray structure is available and its sequence identity to DHPAOs in Cluster 1 is ~21–25%. Based on the crystal structure of CtAPD (PDB codes: 3VSH and 3VHI), the active-site residues His13, His62, and Glu251 are ligated with a mononuclear non-heme Fe(II) center and Tyr129 and His195 are involved in formation of a second sphere metal coordination ( S1 Fig ) [ 42 ]. Based on the sequence analysis ( S1 Fig ), the three active-site residues involved in Fe(II) coordination of CtAPD are all conserved in PaDHPAO as well as other DHPAOs in Cluster 1 (His12, His57, and Glu239 of PaDHPAO as highlighted in yellow in S1 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…The other two active-site residues (highlighted in cyan, Tyr129 and His195) are also conserved in PaDHPAO (Tyr125 and His186) and other DHPAOs in Cluster 1. These two residues are important for second sphere metal-coordination and were shown to be important for catalysis [ 42 ]. (B) The active site structure of CtAPD co-crystallized with 4-nitrocatechol (4NC) shows the involvement of all these conserved residues in metal coordination and substrate binding.…”
Section: Supporting Informationmentioning
confidence: 99%